The effect of preparation temperature and composition on bigel performance as fat replacers. Issue 8 (4th April 2023) - Vershkov, Bela; Davidovich-Pinhas, Maya
Abstract : Consumer awareness of the deleterious effect of saturated fat motivates to find new fat alternatives. Bigels, hybrids of hydrogels and oleogels, are an attractive option for formulating oil-based fat mimetics, particularly lamination fats. Abstract : Consumer awareness of the deleterious effect of a diet rich in saturated fat pushes the food industry to find new fat alternatives. Bigels, hybrids of hydrogels and oleogels, are an attractive option for formulating oil-based fat mimetics, particularly lamination fats. This research explored the characteristics of a hydrogel-in-oleogel bigel, made of candelilla wax and xanthan gum. This study investigated the effect of homogenization temperature, hydrogel : oleogel phase ratio, and storage conditions on the bigel melting profile, mechanical and rheological properties, stability, and the structural characteristics involved. The optimal homogenization temperature that resulted in a smooth, firm, margarine-like texture was 42 °C while higher homogenization temperatures produced lumpy unspreadable bigels and lower ones produced soft and smooth texture. The bigel behavior was related to the formation of a low mobility biphasic system, stabilized in a Pickering mechanism by wax crystals that crystallize at 47 °C, above the homogenization temperature. The phase ratios tested, 15 : 85 to 45 : 55 hydrogel : oleogel, appeared to have a limited effect on any of the bigel characteristics. More specifically, no significant differences in melting temperature, texture parameters, flow behavior, and stability, which are reminiscent of margarine, were detected. These results indicated that hydrogel droplets may serve as active fillers, strengthening the bigel matrix when their amount in the bigel increases and the oleogel, which is the dominant phase, decreases. These findings provide an understanding of the way bigel properties depend on the formulation and preparation, which is valuable in the development of bigel fat replacers and other novel food applications.